Characterization of Antioxidant Compound from Syzygium polyanthum Leaves Fraction Using UHPLC-HRMS - Muhammad Ana Syabana; Nancy Dewi Yuliana; Irmanida Batubara; Dedi Fardiaz (Universitas Jenderal Soedirman, 2021)
The leaves of Syzygium polyanthum is widely used in Indonesia as a spice. It has been reported to have significant antioxidant activity. However, the reports on compounds responsible for the activity are very scarce. The purpose of this research was to characterize the chemical profile of S. polyanthumfractions which showed the highest antioxidant activity. The dried leaves of S. polyanthum were fractionated using the different combination of non-polar to polar solvent, those are n-hexane, acetone, water. Fourteen fractions were collected and analyzed for their DPPH antioxidant activity. The chemical profile of selected fractions was characterized using UHPLC-HRMS to identify compounds that might associate with the antioxidant activity of S. polyanthum. The results showed that at the dose of 500 μg/ml, four fractions showed the highest antioxidant activity with the following order: F9 (acetone:water=80:20), F10 (acetone:water=60:40), F1 (hexane 100%) andF3 (hexane:aceton=80:20). UHPLC-HRMSanalysis successfully identified several compounds in F9 and F10. Gallic acid, pyrogallol, and myricetin were identified in F9. Aconitic acid was identified in F10. All of the identified compounds were previously reported to have antioxidant activity